Proton acceleration enhanced by a plasma jet in expanding foils undergoing relativistic transparency. (16th October 2015) - Powell, H W; King, M; Gray, R J; MacLellan, D A; Gonzalez-Izquierdo, B; Stockhausen, L C; Hicks, G; Dover, N P; Rusby, D R; Carroll, D C; Padda, H; Torres, R; et al.
Abstract: Ion acceleration driven by the interaction of an ultraintense (2 × 10 20 W cm −2 ) laser pulse with an ultrathin ( nm) foil target is experimentally and numerically investigated. Protons accelerated by sheath fields and via laser radiation pressure are angularly separated and identified based on their directionality and signature features (e.g. transverse instabilities) in the measured spatial-intensity distribution. A low divergence, high energy proton component is also detected when the heated target electrons expand and the target becomes relativistically transparent during the interaction. 2D and 3D particle-in-cell simulations indicate that under these conditions a plasma jet is formed at the target rear, supported by a self-generated azimuthal magnetic field, which extends into the expanded layer of sheath-accelerated protons. Electrons trapped within this jet are directly accelerated to super-thermal energies by the portion of the laser pulse transmitted through the target. The resulting streaming of the electrons into the ion layers enhances the energy of protons in the vicinity of the jet. Through the addition of a controlled prepulse, the maximum energy of these protons is demonstrated experimentally and numerically to be sensitive to the picosecond rising edge profile of the laser pulse.